Strategi Penyelenggaraan Pendidikan Inklusif Pada Satuan Paud - Yunitasari, Septiyani Endang; Farista, Dian; Palupi, Diana Indah; Yusnita, Erlin; Rohmah, Siti (Jurnal Pendidikan Indonesia, 2022)
This research is motivated by the curiosity of the authors about inclusive education programs which are actually very effectively developed through Early Childhood Education. Because identifying and determining interventions for ABK will be easier to handle when ABK is still at an early age. The spearhead of inclusive education is PAUD teachers. Because actually early childhood is the golden age, the most effective age for absorbing information. Identification of children who are indicated as part of ABK is the first step to be able to determine and help facilitate early childhood development so that they can grow and develop optimally according to the interests and talents of each child. The approach used in this research is descriptive qualitative, in which the authors try to describe the results of the analysis of implementing inclusive education at early childhood education institutions in the Islamic Kindergarten Inclusion Cahaya Kautsar Jakarta through various observations, interviews and documentation on several aspects, namely a. New student acceptance system, b. owned infrastructure, c. Allocation of funds for the implementation of inclusive education, d. The inclusive education program implementation team, e. Preparation of curriculum models and individual learning programs (PPI), f. Assessment (assessment) and reporting, g. Techniques for socializing the implementation of inclusive education to parents and the community. The obstacles faced in implementing inclusive education at the Cahaya Kautsar Islamic Inclusion Kindergarten in Jakarta include (1) the preparation of activity plans and school budgets has not been optimally structured; (2) facilities and infrastructure are not yet complete and ideal.